Three-dimensional discrete element analysis of the excavation face stability of deep-buried shield tunnels - Xin Huang; Zihao Zhang; Guangyi Yan; Jiaqi Guo; Chong Xu; Qi Liang (Electronic Journal of Structural Engineering)
To study the stability and the influencing factors of shield tunnel excavation face under deep burial conditions, relying on the Bailuyuan shield tunnel in the second phase of the "Water Diversion from the Han to the Wei River" project, we conducted indoor uniaxial compression tests, repose angle tests, and three-dimensional discrete element simulation analysis, calibrated the microparameters of the strata, and constructed a three-dimensional discrete element model of shield tunnel excavation face. The stability and settlement characteristics of the shield tunnel excavation face under different influencing factors were studied. Research results showed that (1) The horizontal displacement of tunnel excavation face and the critical chamber earth pressure ratio increase nonlinearly with the increase of tunnel burial depth; (2) The horizontal displacement of the excavation face, geological settlement, and critical chamber earth pressure ratio all increase with the increase of the cutterhead opening rate; (3) The horizontal displacement of the excavation face and the settlement of the strata increase with the increase of excavation speed and cutterhead rotation rate. The critical chamber earth pressure increases with the increase of cutterhead rotation rate, but is not significantly affected by changes in excavation speed; (4) As to the degree of influence, the burial depth has a significant impact on the horizontal displacement of the excavation face. The influence of the cutterhead opening rate and cutterhead rotation rate on the horizontal displacement of the excavation face is greater than on the settlement of the strata, while the influence of excavation speed on the settlement of the strata is greater than that of the horizontal displacement of the excavation face.